2015
DOI: 10.1177/0004563214568686
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of prescribing thyroxine in primary care

Abstract: Introduction: A practice hypothyroid register is part of the quality and outcomes framework. In literature, the prevalence of hypothyroidism is stated to be 2% but the prevalence, defined from quality and outcomes framework data, is 3.2% in the UK and 3.6% in Plymouth. We sought to investigate the diagnosis of hypothyroidism and reasons for prescription of thyroxine to patients on the hypothyroid register in Plymouth. Methods: A letter was sent to the 10 practices with the highest prevalence of hypothyroidism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
2
0
1
Order By: Relevance
“…Thyroid diseases are considered to be among the most frequent medical conditions in general, and, decisively, they are the most frequent problems of endocrine character with which patients visit their GPs [58-60], while L-thyroxin is in the top ten of the most frequently prescribed and taken medicinal products [58,61].…”
Section: Selenium and The Thyroid Glandmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid diseases are considered to be among the most frequent medical conditions in general, and, decisively, they are the most frequent problems of endocrine character with which patients visit their GPs [58-60], while L-thyroxin is in the top ten of the most frequently prescribed and taken medicinal products [58,61].…”
Section: Selenium and The Thyroid Glandmentioning
confidence: 99%
“…Z kolei L-tyroksyna znajduje się w pierwszej dziesiątce powszechnie przyjmowanych i najczęściej przepisywanych leków [58,61].…”
Section: Selen a Gruczoł Tarczowyunclassified
“…Previous data on the impact of LT4 on fatigue are limited and conflicting. Even though fatigue is a very common symptom in SHypo and often leads to LT4 prescription ( 4 , 5 ), a recent systematic review showed that large randomized controlled trials investigating the benefit of LT4 replacement on fatigue in SHypo are lacking ( 8 ). The only trial, which provided quantitative data for the outcome of fatigue/tiredness, was the TRUST trial.…”
Section: Discussionmentioning
confidence: 99%